The Influence of Problem-Based Learning Model on Students’ Learning Outcomes in Aceh Private University - Rizka, Budi; Lismalinda, Lismalinda (Universitas Pendidikan Ganesha, 2021)
The aim of this study is to analyze the influence of using problem-based learning model in sociolinguistic learning on students learning outcomes of English Education at private universities in Aceh. This study used an experimental method with a research form that is pre-experimental design and one-group pretest-postest design experimental design. The population in this study were 20 students from private universities in Aceh. The sample in this study was the entire population of 20 students who were divided into an experimental group. The research instrument used was the learning outcome in the form of a multiplechoice test of 20 questions. The data collection technique in this study is a measurement technique. Hypothesis test results using t-stat which is obtained in experimental group t-stat (-18.6) < t Critical two-tail (2.093) with an average value of pre-test 59.75 and posttest 78. From the results of these calculations it can be concluded that there is an effect of using problem-based learning models on learning outcomes in sociolinguistic learning of private university students in Aceh.